Comparative Study of Growth Performance, Food Utilization and Survival of the African Catfish Clarias gariepinus (Burchell, 1822) Fingerlings Fed Live Maggot (Musca domestica) and Coppens Commercial Feed - Awom, Iroamachi Emeka; Eyo, Victor Oscar (International Journal of Scientific Research in Science, Engineering and Technology, 2016)
A 70-day feeding experiment was conducted to determine the effect of live maggot and Coppens feed on the growth, food utilization and survival of African catfish (Clarias gariepinus). Triplicate group of fish with a mean initial wet weight of 100.50 ± 2.03 g and length of 9.09 ± 0.11 cm were stocked in six glass aquaria (A1, A2, A3, B1, B2 and B3) measuring 96 cm x 50 cm x29 cm. Fish in A1, A2 and A3 were fed live maggot and B1, B2 and B3 were fed Coppens feed at 5% of their body weight. Growth performance of fish fed Coppens feed evaluated using weight gain (g), length gain (cm), growth rate, specific growth rate, mean growth rate, percentage weight gain and survival varied significantly form fish fed live maggot. Fish fed Coppens feed consumed significantly (P<0.05) more food (1266.77 ± 29.24 g) than fish fed live maggot (784.70± 16.97 g). Food conversion ratio and food conversion efficiency of fish fed Coppens feed (1.56 ± 0.02 and 64.03 ± 0.69 %) was significantly better (P<0.05) than fish fed live maggot (1.66 ± 0.03 and 60.30 ± 0.96%). Proximate analysis of the dry matter (mg/100 g) of maggot meal contained 82.25 ± 0.12 moisture content, 44.56 ± 0.02 crude protein, 5.48 ± 0.05 crude fibre, 24.00± 0.05 mean fat¸ 22.60 ± 0.04 mean carbohydrate and 5.00 ± 0.05 mean ash content while Coppens feed contained 9.00 ± 0.05 moisture content, 42.50 ± 0.42 crude protein, 4.00 ± 0.20 crude fibre, 12.50± 0.05 mean fat, 12.96 ± 0.08 mean carbohydrate and 9.40 ± 0.06 mean ash content. Percentage survival was higher (96.67 ± 5.80 %) in C. gariepinus fed Coppens feed than C. gariepinus fed live maggot (93.33 ± 5.80 %). Water quality parameters including water temperature, pH and dissolved oxygen were within the acceptable range for optimal fish growth and health. The implication of this results is that live maggot is incapable of providing C. gariepinus with all the nutrients required for optimal growth. It is therefore concluded that live maggot can be fed as a supplementary food and not as a complete ration or it can be further processed to maggot meal and used as supplementary protein source to replace or reduce the inclusion of fishmeal which is the most costly feed ingredient in fish feed.
Keywords: Clarias gariepinus; Live maggot; Supplementary protein; Coppens feed; Growth performance; food utilization